2000
DOI: 10.1073/pnas.97.20.10942
|View full text |Cite
|
Sign up to set email alerts
|

A first trial of retrospective collaboration for positional cloning in complex inheritance: Assay of the cytokine region on chromosome 5 by the Consortium on Asthma Genetics (COAG)

Abstract: The central problem of complex inheritance is to map oligogenes for disease susceptibility, integrating linkage and association over samples that differ in several ways. Combination of evidence over multiple samples with 1,037 families supports loci contributing to asthma susceptibility in the cytokine region on 5q [maximum logarithm of odds (lod) ‫؍‬ 2.61 near IL-4], but no evidence for atopy. The principal problems with retrospective collaboration on linkage appear to have been solved, providing far more inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 29 publications
1
23
0
1
Order By: Relevance
“…The initial focus of COAG will be to undertake a combined analysis of linkage data from several studies including this one on chromosome 5q31-33. 29 In conclusion the results of this study support the hypothesis that the 5q31-33 region is linked to susceptibility to asthma, however there was no apparent linkage of measures of atopy in this population. Further typing of both STS markers and polymorphisms in candidate genes within this region will be needed to further understand this linkage and how it relates to both the atopy and asthma phenotypes.…”
Section: Resultssupporting
confidence: 74%
“…The initial focus of COAG will be to undertake a combined analysis of linkage data from several studies including this one on chromosome 5q31-33. 29 In conclusion the results of this study support the hypothesis that the 5q31-33 region is linked to susceptibility to asthma, however there was no apparent linkage of measures of atopy in this population. Further typing of both STS markers and polymorphisms in candidate genes within this region will be needed to further understand this linkage and how it relates to both the atopy and asthma phenotypes.…”
Section: Resultssupporting
confidence: 74%
“…The study showed suggestive linkage for asthma (LOD = 2.6) but no evidence for atopy [8]. Although it is not known whether human genes in the 5q31 cytokine cluster are genetic regulators for atopic disorders, experimental models of asthma have shown the importance of both IL4 and IL13 signaling.…”
mentioning
confidence: 85%
“…This might suggest that these loci are specific to East Asian populations. The loci in regions 5q31-q33 have also been identified as being susceptible to IgE synthesis [17,18]. This region encodes a cluster of cytokine genes, including IL-3, IL-4, IL-5, IL-9, IL-12B and IL-13, which are involved in inflammation in both thyroid and orbit, and IgE synthesis [19].…”
mentioning
confidence: 99%